Alih Wahana Tokoh Sindhir Dalam Wayang Thengul Pada Tari Thengul Di Kabupaten Bojonegoro: Alih Wahana Tokoh Sindhir Dalam Wayang Thengul Pada Tari Thengul Di Kabupaten Bojonegoro - Retnosari, Auliya; Prasetyanti Sekti, Retnayu (Solah, 2025)
Sindhir is a female character known for entertaining the audience in the traditional art form called wayang Thengul. She is recognized for her distinctive personality traits, which include being clever, mischievous, funny, and lively. The transformation from Sindhir Thengul into Thengul dance is an example of a change in medium or "alih wahana." This change involves shifting from the wooden puppet manipulated by a narrator to a human body performing a more communicative and expressive dance. This study aims to describe the process of this change in medium and the transformation of Sindhir's movements from wayang Thengul to Thengul dance in Bojonegoro Regency. The theoretical approach used in this research is based on the concept of "alih wahana" by Sapardi Djoko Damono and the theory of choreography by Sumandiyo Hadi to analyze the movements in Thengul dance. The research method used is descriptive qualitative, with data collection techniques including observation, interviews, and documentation. Data analysis involves data reduction, data presentation, and conclusion drawing, while data validity is ensured through triangulation of sources, techniques, and time. The findings show that the process of changing Sindhir Thengul into Thengul dance maintains her character, though it introduces a new form of expression through more dynamic dance movements. The rigid and limited movements in Sindhir Thengul are transformed into more flexible and artistic movements through stylized dance. Specific movements such as methentheng, jegaguk, trap-trap, and celingak-celinguk have become characteristic features of Thengul dance. The conclusion of this study is that the transformation of Sindhir Thengul into Thengul dance represents a creative and contextual preservation of culture. Through stylized movement and visual interpretation, Thengul dance emerges as a new performance art that remains rooted in local traditions. This dance plays an important role in maintaining the cultural identity of Bojonegoro and has great potential as a medium for education and cultural tourism promotion.